UJI KEMAMPUAN ISOLAT JAMUR Trichoderma spp. SEBAGAI ANTAGONIS Ganoderma boninense DAN PLANT GROWTH PROMOTING FUNGI (PGPF) - Yohan Yogaswara; Radix Suharjo; Suskandini Ratih Dirmawati; Cipta Ginting (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
This study aims to determine the ability of Trichoderma spp. Isolate that collection of Biotechnology Laboratory, Faculty of Agriculture, University of Lampung as an antagonist againstGanoderma boninense and also its ability as a Plant Growth Promoting Fungi (PGPF). Testing of Trichoderma spp. as an antagonist include tests for growth, spore density, and viability. Testing of Trichoderma spp. as PGPF (Plant Growth Promoting Fungi) using cucumber plants F1 variety to obtain the ability of Trichoderma spp. in improving cucumber plant performance. The data obtained were analyzed by analysis of variance and further tested DMRT (Duncan's Multiple Range Test) at 5% level. The results showed that all isolates of Trichoderma spp. can act as an antagonist againstGanoderma boninense. In the PGPF test, there were 3 isolates of Trichoderma spp. which showed the best performance as a plant growth promoting namely L1, L5 and L10 isolates. In addition, these isolates also have good antagonistic.